Hepatitis B DNA quantification in the serum of hepatitis B surface antigen-positive patients in Benghazi - Abdeldaim , Guma M. K.; Abdraba , Ilham O. A.; Qowaider , Salema R. M.; Ali , Marfoua S. (Scientific Journal of University of Benghazi, 2022)
Background: Hepatitis B virus (HBV) infection is a global public health problem, with about 240 million people affected worldwide. Serologic techniques are typically used to diagnose it. However, the decision as to which patient to treat or not remains challenging due to the poor sensitivity of serologic markers as prognostic or severity markers. Viral load (VL) determination using polymerase chain reaction techniques is a useful tool in decision-making. Aim: The aim of this study was to determine the pattern of HBV viral load levels in people of different age and sex groups, to predict the risk of hepatocellular carcinoma and liver cirrhosis in HBsAg positive patients in the east of Libya. Materials and Methods: This is a retrospective and descriptive study. Only one HBV VL test carried out on patients attending the Benghazi university center (from east of Libya) for specialized medical services prior to any HBV targeted therapy were included in the study over a period of 40 months (January 2014 to April 2018) . Hepatitis B DNA VL determinations were analyzed using Microsoft Excel 2010 and Minitab version 17. Results: A total of 431 patients, of whom 51.3% (210) were males and 48.7% (221) were females, were included in the study. Of the 431 patients, 31.3% (135) were below 30 years old, while 68.7% (296) were 30 years old or above. Around 31.1% (134) had measurable assay levels (20 - 2000 (Taq) IU/mL); 21.8% (94) had below 20 IU/mL; and 13.2% (57) had above 2000 IU/ml approximately 21.1% (91) had no detectable HBV DNA in their samples. 12.8% (55) of the patients had levels greater than 20000 IU/mL. The distribution of HBsAg positivity among the patients shows an increasing trend from the lower age group 0-10 to 21-30 in males and from 31-40 in females, then a decreasing trend from 31-40 to 81-90 age group in males and from 41-50 to 81-90 age group in females. A total of 431 patients were investigated for hepatitis B viral load, of whom 90.2% were HBeAg negative and 9.8% were HBeAg positive.